Leadership and Work Discipline on Employee Performance of PT. Indomas Tirta Kencana Abadi - Aaron Filbert; Yeni Ariesa (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of leadership andwork discipline. This type of research is explanatory research. The entire population is 126 employees. Due to a large population, the sampling technique will be reduced by using the Slovin formula with an error tolerance level of 5% so that there are as many as 96 respondents in the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis, and the coefficient of determination as well as simultaneous test, and partial test. The results showed that leadership and work discipline partially, andsimultaneously have a positive, and significant effect on employee performance. Based on the results of this study, the implications for management are to further improve the better leadership and work discipline.